RELIGIOUS SYNCRETISM IN THE LENSES OF JEWISH-BUDHHISM: A RELIGIOUS IDEA IN MODERN AFRICA DEVELOPMENT WUKARI JOURNAL OF HUMANITIES - ZACHARIAH BULUS `` TAKORE; YAKUBU DOMINIC ALKALI; DANIEL BEM APUUIVOM (International Studies Journal)
There are modern attempts to consider understanding God from similar perceptions while being accommodated to your deity. It has to do with mixing orblendingof two religious beliefs or bringingmore religions towards similar goals. Syncretism comes from the word synkretismosin Greek to mix orinvolve other things. The study considers modern development as concerned with the desire or goals of the citizens that are economic in nature, in some instances, it represents the well-being of the citizens by social analyses. A Jewish Buddhist is a person with a Jewish background who believes in the tenets or a form of Buddhism. When the individual practices a particular religion, it may be both Judaism and Buddhism.One typical example could that of the people of Crete in ancient days who always fought themselves, but when enemies threatening to attack them, they combined forces and defeated the enemies. By such act, they defended their interest collectively which enhanced their welfare and growth. A good number of Jews in America and Germany who combined their faith with Buddhism added strength in terms of development capacity economically, technologically and politically to the nations.Africans stand to learn for a better community life and our political, economic and social development.